The childcare center: How to ensure quality childcare practices - Hanafi, Zahyah (Canadian Center of Science and Education, 2015)
Ensuring staff display best practices when handling children at childcare center is a task that requires the management to consistently instill knowledge and skills on child development. This paper will unfold the initiative of a childcare manager who believes that in order to ensure the center provides best services to the children, a research into the level of knowledge and skill on handling children is necessary. Thus, a case study was conducted to identify the key areas of a quality childcare center: staff relationships with children and peers, partnerships with families, programming and evaluation, children’s experiences and learning, protective care and safety, health, nutrition and wellbeing, and managing to support quality.A questionnaire which was adapted from the Quality Improvement Accreditation System (QIAS) model was administered to all the staff at the center. The results revealed that there are areas that reflect staff ability to implement what was taught. However, there are areas that need further training and guidance and there are also areas that urgently require consistent training and monitoring. The paper ends with discussion between the researcher and the manager on ways to enhance staff development.